Ionic intermediate membrane for safety glass and preparation method of ionic intermediate membrane

By combining EMMA-Zn with modified EVA, ionic intermediate films for safety glass are prepared using UV-resistant derivatives and modified fillers, which solves the UV resistance and cost problems in the prior art, and achieves performance improvement and cost reduction Effect.

CN119242187AActive Publication Date: 2025-01-03SHENGDING HIGHTECH MATERIALS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411212123.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2025-01-03
Estimated Expiration
2044-08-30

AI Technical Summary

Technical Problem

The existing safety glass intermediate film has shortcomings in terms of UV resistance and cost, especially the EVA film has poor UV resistance and high cost, while the SGP film terminal price is high and difficult to promote, so it is necessary to develop an ion with low cost and excellent performance. Intermediate film.

Method used

Using EMMA-Zn and modified EVA, an ionic intermediate film for safety glass is prepared by anti-ultraviolet derivative grafting and modified filler surface modification, which improves its UV resistance, impact resistance and bonding properties and reduces UV rays. damage.

Benefits of technology

The ultraviolet resistance, mechanical properties and adhesion properties of the intermediate film are improved, the damage caused by ultraviolet rays to the film is reduced, the cost-effectiveness is improved, and the performance requirements of the ionic intermediate film are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses an ionic intermediate film for safety glass and a preparation method of the ionic intermediate film, and belongs to the technical field of glass laminated films. The intermediate film is prepared from the following components in parts by mass: 60 to 90 parts of EMMA-Zn, 10 to 40 parts of modified EVA (Ethylene Vinyl Acetate) and 1 to 3 parts of modified filler, the modified EVA is obtained by grafting an anti-ultraviolet derivative to EVA, and the anti-ultraviolet derivative contains a benzophenone group and an unsaturated double bond; the modified filler is obtained by carrying out surface modification on a filler by utilizing a modified coupling agent, and the modified coupling agent is obtained by reacting an anti-ultraviolet derivative with mercaptopropyltrimethoxysilane. The modified EVA is obtained by grafting the anti-ultraviolet derivative and the EVA, so that the anti-ultraviolet performance is improved, and the damage of ultraviolet rays to the material is reduced, thereby improving the mechanical properties and optical properties of the material. The anti-ultraviolet derivative contains a benzophenone group and unsaturated double bonds, and the molecular structure contains a quaternary ammonium salt group, so that the anti-ultraviolet derivative can be cross-linked when being applied to the intermediate membrane, and the mechanical property of the intermediate membrane is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of glass lamination, in particular to an ionic intermediate film for safety glass and a preparation method thereof. Background Art

[0002] Laminated glass is a kind of safety glass, which is currently widely used in the fields of construction and automobile. There is an intermediate film in the middle of the laminated glass. Commonly used intermediate films include PVB (polyvinyl butyral), SGP (ethylene-methacrylic acid ionic copolymer), EVA (ethylene-vinyl acetate copolymer), TPU (polyurethane elastomer), etc. After special high temperature and high pressure process treatment, the glass and the intermediate film are bonded into one.

[0003] For example, the patent with publication number CN109796907A discloses an EVA interlayer for high-transmittance and aging-resistant laminated glass and its preparation method, and the patent with publication number CN108892906A discloses an infrared-blocking PVB interlayer and its preparation method. EVA interlayer has good water resistance, fluidity and toughness, but poor UV protection, and is prone to blackening and yellowing after long-term exposure, but it is widely used in the field of civil glass due to its high economic efficiency. PVB interlayer was originally developed for automotive glass. It can meet the performance requirements of automotive glass, but it is sensitive to moisture and needs to add a variety of additives to compensate for its shortcomings, and safety glass needs to be edge-sealed.

[0004] SGP interlayer has high tear strength. Even if the glass is broken, SGP interlayer can still bond the glass to form a temporary structure after the damage, which greatly improves the safety of the glass. SGP interlayer also has good UV resistance and is not easy to yellow. Although SGP interlayer has excellent performance, its terminal price is high and it is difficult to promote it in China. Therefore, it is necessary to develop a low-cost ion-type interlayer for safety glass. Summary of the invention

[0005] In view of the above problems existing in the prior art, an object of the present invention is to provide an ionic intermediate film for safety glass. Another object of the present invention is to provide a method for preparing the intermediate film.

[0006] EMMA is a new type of copolymer with high rigidity, impact resistance and good thermal stability. The EMMA molecular side chain contains methyl methacrylate, which makes it have better bonding properties, and there is no tertiary hydrogen in the molecular chain, which has better UV resistance than EVA. EVA and EMMA are combined to prepare the intermediate film, which can improve the UV resistance of the intermediate film and make it have good toughness and impact resistance.

[0007] In order to solve the above problems, the technical solution adopted by the present invention is as follows: An ionic interlayer for safety glass comprises the following components in parts by weight: 60-90 parts of EMMA-Zn, 10-40 parts of modified EVA, and 1-3 parts of modified filler; The modified EVA is obtained by grafting an anti-ultraviolet derivative onto EVA, wherein the anti-ultraviolet derivative contains a benzophenone group and an unsaturated double bond; The modified filler is obtained by surface-modifying the filler using a modified coupling agent, and the modified coupling agent is obtained by reacting an anti-ultraviolet derivative with mercaptopropyltrimethoxysilane.

[0008] Furthermore, the mass ratio of the filler to the modified coupling agent is 1:1, and the filler is silicon dioxide.

[0009] A method for preparing an ionic intermediate film for safety glass comprises the steps of mixing EMMA-Zn, modified EVA and modified filler, melting and extruding, casting into a film, cooling, pulling and shaping to form the intermediate film.

[0010] Further, the modified EVA is prepared by the following method: The modified EVA is obtained by blending EVA and an anti-ultraviolet derivative, vulcanizing the plate, irradiating the plate with an electron beam, and pelletizing the plate.

[0011] Furthermore, the mass ratio of the EVA to the anti-ultraviolet derivative is 100:(0.5-2.0).

[0012] Furthermore, the process conditions of the electron beam irradiation are: in air atmosphere, the absorbed dose is 90-100 kGy, the dose rate is 4.0×10 5 ~4.4×10 5 kGy•h -1 .

[0013] Furthermore, the modified filler is prepared by the following method: The filler and the modified coupling agent are mixed, ball-milled, cooled to room temperature, washed, centrifuged, dried and ground to obtain the modified filler.

[0014] Furthermore, the modified coupling agent is prepared by the following method: The mercaptopropyltrimethoxysilane, the anti-ultraviolet derivative and the initiator are mixed, the temperature is raised to 63-67° C., and the reaction is carried out for 2.0-2.5 hours to obtain a modified coupling agent.

[0015] Furthermore, the mass ratio of the anti-ultraviolet derivative, mercaptopropyltrimethoxysilane, and the initiator is 10:(5.5-6.0):(0.04-0.12).

[0016] Furthermore, the anti-ultraviolet derivative is prepared by the following method: 4-bromomethylbenzophenone and dimethylaminoethyl methacrylate are mixed in a solvent, and reacted at 20-25° C. for 8-12 hours under the protection of a nitrogen atmosphere to obtain an anti-ultraviolet derivative.

[0017] In the above technical scheme, 4-bromomethylbenzophenone reacts with dimethylaminoethyl methacrylate to obtain an anti-ultraviolet derivative containing a quaternary ammonium group and an allyl group, and the modified EVA is obtained by grafting the anti-ultraviolet derivative with EVA, and the anti-ultraviolet derivative side chains are formed on the EVA molecular chain, so that the spacing between the EVA main chains is increased, which is conducive to the movement of the modified EVA molecular chain, and the elongation at break of the prepared intermediate film is improved. The quaternary ammonium group in the modified EVA forms a strong bond energy on the surface of glass and inorganic filler, thereby improving the bonding force of the prepared intermediate film, improving the mechanical properties of the intermediate film, and being able to improve its optical properties to a certain extent.

[0018] In the above technical scheme, the unsaturated double bonds of the anti-ultraviolet derivatives undergo a thermal click reaction with the mercapto group in mercaptopropyltrimethoxysilane through the initiator AIBN to obtain a siloxane containing anti-ultraviolet groups and quaternary ammonium salt groups, which is recorded as a modified coupling agent. The surface of the filler is modified by it, the number of anti-ultraviolet groups in the intermediate film system is increased, and the surface of the filler is organic and has ultraviolet absorption characteristics; the ultraviolet shielding ability of the synergistic filler silica is further improved to further improve the anti-ultraviolet performance of the intermediate film; and it helps to improve the compatibility between the filler and the modified EVA, so as to fully exert the filler performance in the intermediate film. The surface quaternary ammonium salt group of the modified filler can form a strong bond energy on the glass surface, which improves the bonding force of the intermediate film. The combination of modified EVA and EMMA-Zn further improves the toughness and impact resistance of the intermediate film, so that it meets the performance requirements of the ionic intermediate film.

[0019] Compared with the prior art, the present invention has the following beneficial effects: (1) The method for preparing an ionic interlayer for safety glass of the present invention is to obtain a modified EVA by grafting an anti-ultraviolet derivative with EVA, thereby improving the anti-ultraviolet performance, reducing the damage of ultraviolet rays to the interlayer, and helping to improve its mechanical properties and optical properties. The anti-ultraviolet derivative contains a benzophenone group and an unsaturated double bond, and contains a quaternary ammonium salt group in the molecular structure, which can form a strong bond energy on the inorganic filler and the glass surface, thereby improving the mechanical properties and bonding properties of the prepared interlayer. The combination of modified EVA and EMMA-Zn further improves the toughness and impact resistance of the interlayer, so that it meets the performance requirements of the ionic interlayer.

[0020] (2) The method for preparing an ionic interlayer for safety glass of the present invention improves the adhesion of the interlayer to glass, improves the dispersibility of silica in the interlayer, and improves the compatibility of the two, so that the silica is more evenly distributed in the material to form a more stable composite material. The modified coupling agent is prepared with raw materials such as anti-ultraviolet derivatives, and can be compounded with the filler while improving the compatibility of the filler, thereby improving the resistance of the prepared interlayer to ultraviolet rays. DETAILED DESCRIPTION

[0021] The present invention is further described below in conjunction with specific embodiments.

[0022] In the following specific implementations, EMMA-Zn: Brand 9520, from Dow Chemical, USA; EVA: CAS number: 24937-78-8, derived from MacLean reagent; Silicon dioxide, CAS number: 14808-60-7, from Shandong Pingju Biotechnology Co., Ltd.; Dimethylaminoethyl methacrylate (CAS No. 2867-47-2), derived from MacLean's reagent; 4-Bromomethylbenzophenone (CAS No. 32752-54-8), derived from MacLean's reagent; Ultraviolet absorber (CAS No.: 131-56-6) is from Hubei Watson Chemical Technology Co., Ltd.

[0023] The rest are commercially available conventional chemicals.

[0024] The thickness of the intermediate film is 0.35mm~0.75mm.

[0025] The following specific implementation method is a laboratory test and can be scaled up in equal proportions.

[0026] Example 1 A method for preparing an ionic intermediate film for safety glass, comprising the following processes: Step (1) Preparation of modified EVA: 4-bromomethylbenzophenone and dimethylaminoethyl methacrylate were mixed in acetone, and reacted at 20°C for 10 hours under nitrogen atmosphere. The white solid was filtered out, and the other part of the solid obtained after evaporating the filtrate was washed with ether. The solids obtained twice were combined and recrystallized with acetone to obtain an anti-ultraviolet derivative. The ratio of 4-bromomethylbenzophenone to acetone was 2.5 g / 100 mL; the molar ratio of 4-bromomethylbenzophenone to dimethylaminoethyl methacrylate was 1:1.

[0027] EVA and anti-ultraviolet derivatives were mixed at 90°C for 10 min, flat-plate vulcanized at 110°C and 10 MPa, pressed into 1 mm sheets, hot-pressed for 2 min, preheated for 3 min before hot-pressing, and electron beam irradiated in air atmosphere with an absorbed dose of 90 kGy and a dose rate of 4.4×105 kGy•h -1 , pelletized to obtain modified EVA; the mass ratio of EVA to the anti-ultraviolet derivative is 100:0.5.

[0028] Step (2) Preparation of modified filler: The mercaptopropyl trimethoxysilane, the anti-ultraviolet derivative and the initiator are mixed, the temperature is raised to 63°C, and the reaction is carried out for 2 hours to obtain a modified coupling agent; the mass ratio of the anti-ultraviolet derivative, the mercaptopropyl trimethoxysilane and the initiator is 10:5.5:0.04; the initiator is azobisisobutyronitrile.

[0029] The silica and modified coupling agent were mixed and ball-milled at a ball-to-material mass ratio of 1:1, a ball mill speed of 400 r / min, and the forward and reverse rotations were performed for 2 h each; the mixture was cooled to room temperature, washed, centrifuged at a centrifugal speed of 5000 r / min, and the centrifugal time was 5 min; the mixture was dried, ground at a grinding machine speed of 200 r / min, and ground for 30 min to obtain a modified filler, in which the mass ratio of silica to the modified coupling agent was 1:1.

[0030] Step (3) Preparation of intermediate film: EMMA-Zn, modified EVA and modified filler are mixed and conveyed to the barrel of an extruder through equipment. The molten mixture in the extruder is cast into a film with a melting temperature of 70° C. through the rotation of the screw, and then cooled, pulled and shaped to form an intermediate film with a thickness of 0.35 mm. The mass ratio of EMMA-Zn, modified EVA and modified filler is 90:10:1.

[0031] Example 2 A method for preparing an ionic intermediate film for safety glass, comprising the following processes: Step (1) Preparation of modified EVA: 4-bromomethylbenzophenone and dimethylaminoethyl methacrylate were mixed in acetone, and reacted at 22°C for 10 hours under nitrogen atmosphere. The white solid was filtered out, and the other part of the solid obtained after evaporating the filtrate was washed with ether. The solids obtained twice were combined and recrystallized with acetone to obtain an anti-ultraviolet derivative. The ratio of 4-bromomethylbenzophenone to acetone was 2.5 g / 100 mL; the molar ratio of 4-bromomethylbenzophenone to dimethylaminoethyl methacrylate was 1:1.3.

[0032] EVA and anti-ultraviolet derivatives were mixed at 92°C for 13 minutes, flat-plate vulcanized at 112°C and 10 MPa, pressed into 1 mm sheets, hot-pressed for 2 minutes, preheated for 3 minutes before hot-pressing, and electron beam irradiated in air atmosphere with an absorbed dose of 95 kGy and a dose rate of 4.6×105 kGy•h -1 , pelletized to obtain modified EVA; the mass ratio of EVA to the anti-ultraviolet derivative is 100:1.

[0033] Step (2) Preparation of modified filler: The mercaptopropyl trimethoxysilane, the anti-ultraviolet derivative and the initiator are mixed, the temperature is raised to 65°C, and the reaction is carried out for 2.3 hours to obtain a modified coupling agent; the mass ratio of the anti-ultraviolet derivative, the mercaptopropyl trimethoxysilane and the initiator is 10:5.7:0.08; the initiator is azobisisobutyronitrile AIBN.

[0034] The silica and modified coupling agent were mixed and ball-milled at a ball-to-material mass ratio of 1:1, a ball mill speed of 450 r / min, and the forward and reverse rotations were performed for 2.3 h each; the mixture was cooled to room temperature, washed, centrifuged at a centrifugal speed of 5500 r / min, and the centrifugal time was 7 min; the mixture was dried, ground at a grinding machine speed of 250 r / min, and ground for 32 min to obtain a modified filler, in which the mass ratio of silica to the modified coupling agent was 1:1.

[0035] Step (3) is the same as step (3) in Example 1, and an intermediate film is obtained. The mass ratio of EMMA-Zn, modified EVA and modified filler is 75:25:2, and the thickness of the intermediate film is 0.55 mm.

[0036] Example 3 A method for preparing an ionic intermediate film for safety glass, comprising the following processes: Step (1) Preparation of modified EVA: 4-bromomethylbenzophenone and dimethylaminoethyl methacrylate are mixed in acetone, and reacted at 25°C for 10 hours under a nitrogen atmosphere; a white solid is filtered out, and the other part of the solid obtained after evaporating the filtrate is washed with ether, and the solids obtained from the two times are combined and recrystallized with acetone to obtain an anti-ultraviolet derivative; the ratio of 4-bromomethylbenzophenone to acetone is 2.5 g / 100 mL; the molar ratio of 4-bromomethylbenzophenone to dimethylaminoethyl methacrylate is 1:1.5.

[0037] EVA and anti-ultraviolet derivatives were mixed at 92°C for 15 min, flat-plate vulcanized at 115°C and 10 MPa, pressed into 1 mm sheets, hot-pressed for 2 min, preheated for 3 min before hot-pressing, and electron beam irradiated in air atmosphere with an absorbed dose of 100 kGy and a dose rate of 4.8×105 kGy•h -1, pelletized to obtain modified EVA; the mass ratio of EVA to the anti-ultraviolet derivative is 100:2.

[0038] Step (2) Preparation of modified filler: Mercaptopropyltrimethoxysilane, anti-ultraviolet derivatives and initiators are mixed, heated to 67°C, and reacted for 2.5 hours to obtain a modified coupling agent; the mass ratio of the anti-ultraviolet derivative, mercaptopropyltrimethoxysilane and initiator is 10:6:0.12; the initiator is azobisisobutyronitrile AIBN.

[0039] The silica and modified coupling agent were mixed and ball-milled at a ball-to-material mass ratio of 1:1, a ball mill speed of 500 r / min, and the forward and reverse rotations were performed for 2.5 h each; the mixture was cooled to room temperature, washed, centrifuged at a centrifugal speed of 6000 r / min, and the centrifugal time was 10 min; the mixture was dried, ground at a grinding machine speed of 300 r / min, and ground for 35 min to obtain a modified filler, in which the mass ratio of silica to the modified coupling agent was 1:1.

[0040] Step (3) is the same as step (3) in Example 1, and an intermediate film is obtained; the mass ratio of EMMA-Zn, modified EVA, and modified filler is 60:40:3, and the thickness of the intermediate film is 0.75 mm.

[0041] Comparative Example 1 A method for preparing a glass interlayer film comprises the following processes: Step (1) Preparation of modified EVA: EVA, 4-propyleneoxy-2-hydroxybenzophenone and dimethyldiallylammonium chloride were mixed at 90°C for 10 min, vulcanized at 110°C and 10 MPa, pressed into 1 mm thick sheets, hot pressed for 2 min, preheated for 3 min before hot pressing, and irradiated with electron beams in air atmosphere with an absorbed dose of 90 kGy and a dose rate of 4.4×105 kGy•h -1 , pelletized to obtain modified EVA; the mass ratio of EVA, 4-propyleneoxy-2-hydroxybenzophenone, and dimethyldiallylammonium chloride is 100:0.3:0.2.

[0042] Step (2) Preparation of modified filler: Silica and coupling agent (KH-570) were mixed and ball-milled at a ball-to-material mass ratio of 1:1, a ball mill speed of 400 r / min, and the forward and reverse rotations were performed for 2 h each; cooled to room temperature, washed, centrifuged at a centrifugal speed of 5000 r / min, a centrifugal time of 5 min, dried, ground at a grinding machine speed of 200 r / min, and ground for 30 min to obtain a modified filler, in which the mass ratio of silica to KH-570 was 1:1.

[0043] Step (3) Preparation of intermediate film: EMMA-Zn, modified EVA and modified filler are mixed and conveyed to the barrel of an extruder through equipment. The molten mixture in the extruder is cast into a film with a melting temperature of 70° C. through the rotation of the screw, and then cooled, pulled and shaped to form an intermediate film with a thickness of 0.35 mm. The mass ratio of EMMA-Zn, modified EVA and modified filler is 60:10:1.

[0044] Comparative Example 2 A method for preparing an intermediate film for glass, comprising the following processes: Step (1) Preparation of modified EVA: EVA and dimethyldiallylammonium chloride were mixed at 90°C for 10 min, flat-plate vulcanized at 110°C and 10 MPa, pressed into 1 mm sheets, hot-pressed for 2 min, preheated for 3 min before hot-pressing, and electron beam irradiated in air atmosphere with an absorbed dose of 90 kGy and a dose rate of 4.4×105 kGy•h -1 , pelletized to obtain modified EVA; the mass ratio of EVA and dimethyldiallylammonium chloride is 100:0.2.

[0045] Step (2) Preparation of modified filler: Silica and coupling agent (KH-570) were mixed and ball-milled at a ball-to-material mass ratio of 1:1, a ball mill speed of 400 r / min, and the forward and reverse rotations were performed for 2 h each; cooled to room temperature, washed, centrifuged at a centrifugal speed of 5000 r / min, a centrifugal time of 5 min, dried, ground at a grinding machine speed of 200 r / min, and ground for 30 min to obtain a modified filler, in which the mass ratio of silica to KH-570 was 1:1.

[0046] Step (3) Preparation of an intermediate film: EMMA-Zn, modified EVA, modified filler and anti-ultraviolet absorber are mixed with a melting temperature of 70°C, and the mixture is transferred to the barrel of an extruder through an equipment. The molten mixture in the extruder is cast into a film through the rotation of the screw, and then cooled, pulled and shaped to form an intermediate film. The thickness of the intermediate film is 0.35 mm. The mass ratio of EMMA-Zn, modified EVA, modified filler and anti-ultraviolet absorber is 60:10:1:0.3.

[0047] Comparative Example 3 A method for preparing an intermediate film for glass, comprising the following processes: Step (1) Preparation of modified filler: Silica and coupling agent (KH-570) were mixed and ball-milled at a ball-to-material mass ratio of 1:1, a ball mill speed of 400 r / min, and the forward and reverse rotations were performed for 2 h each; cooled to room temperature, washed, centrifuged at a centrifugal speed of 5000 r / min, the centrifugal time was 5 min, dried, ground at a grinding machine speed of 200 r / min, and ground for 30 min to obtain a modified filler, wherein the mass ratio of silica to KH-570 was 1:1; Step (2) Preparation of an intermediate film: EMMA-Zn, EVA, modified filler and ultraviolet absorber are melt-mixed at a melting temperature of 70°C, and are transferred to the barrel of an extruder through an equipment. The molten mixture in the extruder is cast into a film through the rotation of the screw, and then cooled, pulled and shaped to form an intermediate film. The thickness of the intermediate film is 0.35 mm. The mass ratio of EMMA-Zn, EVA, modified filler and ultraviolet absorber is 60:10:1:0.3.

[0048] Test experiment: The intermediate films obtained in Examples 1 to 3 and Comparative Examples 1 to 3 were taken to prepare samples, and their properties were tested respectively and the test results were recorded.

[0049] Tensile performance test: GB / T 528 is used as the reference standard to test the tensile performance of the sample. The sample is dumbbell-shaped and the tensile rate is 100 mm / min.

[0050] Adhesion strength test: GB / T 2790 is used as the reference standard to test the adhesion strength between the sample and the glass; the interlayer sample is placed on the glass surface and laminated. The lamination process conditions are: lamination temperature is 145°C and lamination time is 10 minutes.

[0051] UV resistance test: The prepared interlayer film was placed in a U-3010 spectrometer for UV spectrum detection, with a scanning wavelength range of 220-400nm and a scanning speed of 600nm•min -1 , step length 1nm. After UV irradiation for 144h, the tensile properties of the samples were tested again.

[0052] The test results are as follows:

[0053] According to the data in the above table, we can clearly draw the following conclusions: The intermediate films obtained in Examples 1-3 are compared with the intermediate films obtained in Comparative Examples 1-3. The test results show that: Compared with Comparative Example 1, the intermediate films obtained in Examples 1-3 have more excellent tensile strength, bonding strength and anti-ultraviolet tensile strength, which fully demonstrates that the setting of EMMA-Zn, modified EVA and modified filler in the present invention can effectively improve the tensile strength, bonding strength and anti-ultraviolet tensile strength of the prepared intermediate films.

[0054] Compared with Example 1, in Comparative Example 1, the anti-ultraviolet derivative is replaced with 4-propyleneoxy-2-hydroxybenzophenone and dimethyldiallyl ammonium chloride, and 4-propyleneoxy-2-hydroxybenzophenone and dimethyldiallyl ammonium chloride are grafted with EVA during electron beam irradiation; the modified filler is prepared from KH-570 modified silica. The intermediate film obtained in Comparative Example 1 has a change in the branched chain of the modified EVA component, and the anti-ultraviolet stability is reduced, so that its tensile strength and tensile strength data after ultraviolet aging are significantly reduced.

[0055] Compared with Example 1, in Comparative Example 2, the anti-ultraviolet derivative is replaced with dimethyldiallylammonium chloride, and the intermediate film is a blend of modified EVA, modified filler and ultraviolet absorber; the anti-ultraviolet absorber does not form a branch chain on the EVA molecule. It can be seen from the data in the above table that the tensile strength, adhesive strength and tensile strength data after ultraviolet aging of the intermediate film obtained in Comparative Example 2 are all reduced.

[0056] Compared with Example 1, the intermediate film obtained in Comparative Example 3 is prepared by blending the intermediate film of EVA, modified filler and ultraviolet absorber. The intermediate film obtained in Comparative Example 3 has a significant decrease in tensile strength, bonding strength and tensile strength data after ultraviolet aging. The reason is that the intermediate film obtained in Comparative Example 3 is a blend of EVA, modified filler and ultraviolet absorber, and the anti-ultraviolet absorber does not form a branch chain on the EVA molecule, nor does it form a quaternary ammonium salt group, which reduces the anti-ultraviolet stability of the modified EVA, and weakens the bonding ability between the modified EVA and the glass and filler, which is reflected in the decrease in the tensile strength, bonding strength and tensile strength of the prepared intermediate film after ultraviolet aging. It can be seen that the preparation process of the intermediate film and the setting of the components used in the present application can promote the comprehensive improvement of its mechanical properties, bonding properties and anti-ultraviolet properties.

[0057] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.

[0058] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An ionomeric interlayer for safety glass, characterized in that: The composition comprises the following components in parts by weight: 60-90 parts of EMMA-Zn, 10-40 parts of modified EVA, and 1-3 parts of modified filler; The modified EVA is obtained by grafting an anti-ultraviolet derivative onto EVA, wherein the anti-ultraviolet derivative contains a benzophenone group and an unsaturated double bond; The modified filler is obtained by surface-modifying the filler using a modified coupling agent, and the modified coupling agent is obtained by reacting an anti-ultraviolet derivative with mercaptopropyltrimethoxysilane.

2. The ionic interlayer film for safety glass according to claim 1, characterized in that: The mass ratio of the filler to the modified coupling agent is 1:1, and the filler is silicon dioxide.

3. A method for preparing an ionic intermediate film for safety glass according to any one of claims 1 or 2, characterized in that: The EMMA-Zn, modified EVA and modified filler are mixed, melt-extruded, cast into a film, cooled, pulled and shaped to form an intermediate film.

4. The method for preparing an ionic intermediate film for safety glass according to claim 3, characterized in that: The modified EVA is prepared by the following method: The modified EVA is obtained by blending EVA and an anti-ultraviolet derivative, vulcanizing the plate, irradiating the plate with an electron beam, and pelletizing the plate.

5. The method for preparing an ionic intermediate film for safety glass according to claim 4, characterized in that: The mass ratio of the EVA to the anti-ultraviolet derivative is 100:(0.5-2.0).

6. The method for preparing an ionic intermediate film for safety glass according to claim 4, characterized in that: The process conditions of the electron beam irradiation are: in air atmosphere, the absorbed dose is 90-100 kGy, the dose rate is 4.0×10 5 ~4.4×10 5 kGy•h -1 .

7. The method for preparing an ionic intermediate film for safety glass according to claim 3, characterized in that: The modified filler is prepared by the following method: The filler and the modified coupling agent are mixed, ball-milled, cooled to room temperature, washed, centrifuged, dried and ground to obtain the modified filler.

8. The method for preparing an ionic intermediate film for safety glass according to claim 7, characterized in that: The modified coupling agent is prepared by the following method: Mix mercaptopropyltrimethoxysilane, anti-ultraviolet derivatives and initiators, raise the temperature to 63-67°C, and react for 2.0-2.5 hours to obtain a modified coupling agent.

9. The method for preparing an ionic intermediate film for safety glass according to claim 8, characterized in that: The mass ratio of the anti-ultraviolet derivative, mercaptopropyltrimethoxysilane and the initiator is 10:(5.5-6.0):(0.04-0.12).

10. The method for preparing an ionic intermediate film for safety glass according to claim 4 or 8, characterized in that: The anti-ultraviolet derivative is prepared by the following method: 4-bromomethylbenzophenone and dimethylaminoethyl methacrylate are mixed in a solvent, and reacted at 20-25° C. for 8-12 hours under the protection of a nitrogen atmosphere to obtain an anti-ultraviolet derivative.

Citation Information

Patent Citations

  • Benzophenone initiating agent with aqueous reactivity and synthetic method thereof

    CN102504055A

  • Ultraviolet light absorber as well as preparation method and application thereof

    CN113444123A

  • Ionization modified ethylene-acrylic acid copolymer and preparation method thereof, and ionic polymer intermediate membrane and application thereof

    CN113980159A

  • Super-hydrophobic nano silicon dioxide and preparation method thereof

    CN117843006A

  • Polymerizable compositions and laminated articles bonded thetewith

    GB1424443A